Primary mucinous adenocarcinoma of appendix treated with chemotherapy and radiotherapy: a case report - Topkan, Erkan; Polat, Yimaz; Karaoglu, Aziz (Pensiero Scientifico Editor, 2008)
A rare case of primary appendiceal mucinous adenocarcinoma is reported. The presenting signs and symptoms were suggestive of acute appendicitis. An appendectomy was performed resulting in a histological diagnosis of grade 2 mucinous adenocarcinoma of the appendix. The patient was referred to our clinic where he underwent a complementary right hemicolectomy with lymph node dissection. Two of the 17 resected lymph nodes were tumor positive but there was no residual tumor in the hemicolectomy specimen. The patient was staged as T4N1M0 and adjuvant multi-modality treatment was planned because he was considered at high risk for local-regional recurrence and distant metastasis. Three cycles of capecitabine 1250 mg/m(2) on days 1-14 and oxaliplatin 130 mg/m(2) on day 1, every 21 days (CAPOX) were administered, then a total dose of 50.4 Gy external-beam radiation therapy was delivered to the primary tumor region and 45 Gy to the lymphatics, and finally 3 further cycles of the CAPOX regimen were administered. Multimodality treatment was well tolerated by the patient, who is still alive 25 months after the hemicolectomy procedure with no evidence of disease progression.
Keywords: appendix; mucinous adenocarcinoma; secondary hemicolectomy; chemotherapy; radiation therapy